A Co-delivery System Based on a Dimeric Prodrug and Star-Shaped Polymeric Prodrug Micelles for Drug Delivery - Zhou, Man; Luo, Yan; Zeng, Weijia; Yang, Xiaoqing; Chen, Tingting; Zhang, Lulu; He, Xiaoyan; Yi, Xiuguang; Li, Yongxiu; Yi, Xiaoqing (Frontiers in Chemistry, 2021)
Chemotherapy is one of the commonly used therapies for the treatment of malignant tumors. Insufficient drug loading capacity is the major challenge for polymeric micelles based drug delivery systems of chemotherapy. Here, the redox-responsive star-shaped polymeric prodrug (PSSP) and the dimeric prodrug of paclitaxel (PTX) were prepared. Then, the dimeric prodrug of PTX (diPTX) was loaded into the core of the star-shaped polymeric prodrug micelles of PSSP by hydrophobic interaction forming the redox-responsive prodrug micelles of diPTX@PSSP for intracellular drug release in tumor cells. The hydrodynamic diameter of diPTX@PSSP nanoparticles was 114.3 nm ± 2.1 (PDI = 0.219 ± 0.016) nm, the micelles had long-term colloidal stability and the drug loading content (DLC) of diPTX and PTX is 16.7% and 46.9% respectively. The prepared micelles could broke under the reductive microenvironment within tumor cells, as a result, the dimeric prodrug of diP and polymeric prodrug micelles of PSSP were rapidly disassembled, leading to the rapid release of intracellular drugs. In vitro release studies showed that under the condition of reduced glutathione (GSH) (10 mM), the release of PTX was significantly accelerated with approximately 86.6% released within 21 hours. And the released PTX in cytoplasm could promote the disintegration of microtubules and induce cell apoptosis. These results indicated that the new type of this reduction-sensitive nanodrug delivery system based on dimeric prodrug@polymeric prodrug micelles would be a promising technology in chemotherapy.